2014
DOI: 10.1038/ja.2014.99
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activities of rifampin, colistin, sulbactam and tigecycline tested alone and in combination against extensively drug-resistant Acinetobacter baumannii

Abstract: The aim of this study was to investigate the in vitro activities of rifampin, colistin, sulbactam and tigecycline alone and in combination against extensively drug-resistant Acinetobacter baumannii (XDR-Ab). Twenty-five XDR-Ab strains were isolated from patients. Broth microdilution assay was used to determine the minimum inhibitory concentration (MIC) for rifampin, colistin, sulbactam and tigecycline against XDR-Ab strains. The checkerboard microdilution method was used to determine the in vitro activities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 16 publications
4
28
1
2
Order By: Relevance
“…In a study in 2013, Lee et al [29] have shown that the combination of colistin and rifampin increased killing rate of both multidrug resistant colistin susceptible and resistant A. baumannii and that combination therapy prevented or suppressed the emergence of colistin-resistant subpopulations. Dong et al [30] showed that the combinations of Col+Rif, rifampin-sulbactam, rifampin-tigecycline and sulbactam-tigecycline showed good in vitro activities (addictive or partially synergistic) against extensively drug-resistant A. baumannii isolates even at subinhibitory concentrations. Our findings were in accordance with these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in 2013, Lee et al [29] have shown that the combination of colistin and rifampin increased killing rate of both multidrug resistant colistin susceptible and resistant A. baumannii and that combination therapy prevented or suppressed the emergence of colistin-resistant subpopulations. Dong et al [30] showed that the combinations of Col+Rif, rifampin-sulbactam, rifampin-tigecycline and sulbactam-tigecycline showed good in vitro activities (addictive or partially synergistic) against extensively drug-resistant A. baumannii isolates even at subinhibitory concentrations. Our findings were in accordance with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies reported synergistic effects between diverse drugs for the treatment of Acinetobacter [26,[29][30][31][32]37] . However, more in vivo studies about these combinations are needed to provide high grade of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Clavulanic acid alone has been reported to have an MIC as low as 1 mg/mL against N. gonorrhoeae (Wise et al 1978); sulbactam has modest activity against wild-type Acinetobacter spp. 8 and 10 mg/mL, respectively (Jacoby and Sutton 1989;Fass et al 1990), but does not retain activity against isolates with multiple resistance mechanisms (Dong et al 2014). None of these inhibitors is effective in inhibiting the hydrolytic activity of MBLs (Bush 2015), and their modest activity against serine carbapenemases does not translate into clinical susceptibility (Yigit et al 2003;Woodford et al 2004) owing, at least in part, to the presence of multiple b-lactamases in the producing organisms (Moland et al 2007).…”
Section: B-lactamase Inhibitorsmentioning
confidence: 99%
“…27 Principe et al 7 for the first time reported that they have noticed the synergy between TGC and CL by TK method in one A. baumannii isolate. In two studies conducted by CB method in TGC-CL combination 28 and in TGC-sulbactam, TGC-CL combinations 29 a synergistic effect was observed.…”
Section: Discussionmentioning
confidence: 99%